2017
DOI: 10.1371/journal.pone.0181831
|View full text |Cite
|
Sign up to set email alerts
|

Receiver Operating Characteristic curve analysis determines association of individual potato foliage volatiles with onion thrips preference, cultivar and plant age

Abstract: Tomato spotted wilt virus (TSWV) causes sporadic but serious disease in Australian potato crops. TSWV is naturally spread to potato by thrips of which Thrips tabaci is the most important. Prior studies indicated possible non-preference of potato cultivars to T. tabaci. Select potato cultivars were assessed for non-preference to T. tabaci in paired and group choice trials. Cultivars ‘Bismark’, ‘Tasman’ and ‘King Edward’ were less preferred than ‘Atlantic’, ‘Russet Burbank’ and ‘Shepody’. Green leaf volatiles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Our study suggested that adult female thrips could use olfactory cues to select plants for their offspring. Solid-phase microextraction (SPME) is considered to be a useful tool to get a realistic picture of the volatiles emitted from fresh tomato [49], and it was used to study volatiles from TSWV-infected plants [49][50][51]. We used SPME fibers to collect volatile compounds from mixed-infected plants and compared the collected compounds with those emitted by healthy or single virus-infected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that adult female thrips could use olfactory cues to select plants for their offspring. Solid-phase microextraction (SPME) is considered to be a useful tool to get a realistic picture of the volatiles emitted from fresh tomato [49], and it was used to study volatiles from TSWV-infected plants [49][50][51]. We used SPME fibers to collect volatile compounds from mixed-infected plants and compared the collected compounds with those emitted by healthy or single virus-infected plants.…”
Section: Discussionmentioning
confidence: 99%
“…By dividing all observations that are part of the actual class by the percentage of observations that were correctly predicted to be positive, recall-also known as sensitivity-is calculated. [34].…”
Section: The Resultsmentioning
confidence: 99%
“…. ROC analysis is currently widely used in nearly all fields of science, including artificial intelligence [37], and in agriculture [39,40]. e ROC provides a measure of how well the fitted model distinguishes true cases from true noncases.…”
Section: Area Under Roc Curve (Auroc)mentioning
confidence: 99%
“…e ROC provides a measure of how well the fitted model distinguishes true cases from true noncases. e AUROC can also be interpreted as the average probability of correctly visualizing a positive case across all possible cutoff points of the predictor [40]. e value of the area under the ROC curve ranges between 0 and 1, which can be expressed as a percentage.…”
Section: Area Under Roc Curve (Auroc)mentioning
confidence: 99%